Isokinetic Assessment of the Wrist Muscles in Females With Fibromyalgia - Hayal GÜLER,; Mustafa Turgut YILDIZGÖREN,; Nilgun ÜSTÜN,; Hacer PAKSOY,; Ayşe Dicle TURHANOĞLU, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate wrist muscle strength and muscle fatigue in females with fibromyalgia syndrome (FMS) and compare the results with those of healthy controls. Patients and methods: Thirty consecutive female FMS patients (mean age 39.8±6.7 years; range 25 to 49 years) and 50 age and body mass index similar healthy females (mean age 35.4±7.9 years; range 27 to 48 years) were enrolled. Patients’ clinical characteristics were recorded and symptoms were evaluated by the Fibromyalgia Impact Questionnaire. In addition to the demographic characteristics, physical activities of all subjects were questioned, isokinetic muscle performance was measured, and fatigue index was calculated by endurance test. Results: The peak torque values of the wrist extensor and flexor muscles (at an angular velocity of 90°/second) were higher in the control group than in the FMS group (both p<0.01). There were no differences between the groups in terms of the fatigue indexes of the flexor and extensor muscles of the wrist (both p>0.05). While there were differences between the groups regarding weekly hours of walking (p=0.01) and house cleaning (p<0.001), no differences were determined for weekly hours of bicycling, gardening, doing sports, or total physical activity. There was no correlation between the peak torque values and clinical characteristics in FMS group. Conclusion: Patients with FMS had decreased muscle strength compared to healthy controls. Further studies with larger participants are needed to explain the relationship between upper limb muscle performance and FMS, as well as the underlying pathogenesis.